Análise de perigos e pontos críticos de controle em dietas enterais manipuladas no Hospital de Clínicas da Universidade Federal de Uberlândia - Muniz, Cinara Knychala (2005)
In spite of the good results in food industry and institutional restaurants the Hazard Analysis Critical Control Point (APPCC) system has not been widely applied to the problems of hospital infection control. The aim of this study was to investigate the microbiological quality of blenderized (powder and artisanal) and ready-to-use feed Pré and Pós implementation of APPCC system in Brazilian teaching hospital. The presence of mesophilics, total and fecal coliforms, Staphylococcus aureus, Bacillus cereus, C. perfringens, Salmonella spp and Listeria was researched in 76 samples of enteral feeds into two different Groups of foodhandlers (one Group worked in a day and other worked in the next day) and stored at 4ºC for until 18 h, critical control points as blenders were also researched, surface of cans, water and foodhandlers nostril and handlers. Artisanal and powder feeds Pré the APPCC system was around 50% above the recommended, and Pós the APPCC system implementation these value increased to 57 % and 97% above the recommended respectively. The ready to use feeds conserved 100% adequacy in two moments, Pré and Pós APPCC. Blenders used in preparing of enteral feeds were found to be the important source of contamination. It was noticed the importance of personnel hygiene mainly in one of two Groups of workers Pré implementation of the APPCC system. Contamination of enteral feeds can be reduced and powder feeds can be available with microbiologic quality similarly to ready-to-use diets if principles of the APPCC system are implemented.